Pengaruh training dan skill terhadap performance Pekerja Migran Indonesia (PMI) di luar negeri pada kantor Badan Pelindungan Pekerja Migran Indonesia (BP2MI) Bekasi - Adi Jaya, Umban; Febriyanti, Intan Rieke; Maryanto, Toni (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Humans often experience change and growth, which can lead to all kinds of challenges that need to be faced and overcome properly. The achievement of company goals can be realized if the company's human resources show good work performance. The purpose of this study was to see how different dimensions or variables, such as training and skills, affected the performance of Indonesian migrant workers abroad. The research method used was a survey method using a questionnaire distributed to 89 people using the Isaac and Michael table equations. While the instrument quality testing techniques include validity and reliability tests, and data analysis techniques such as descriptive analysis and correlation, as well as hypothesis testing using multiple linear regression analysis. The results of this study indicate that two independent variables have a significant effect on performance, namely the training variable with a t-value of 0.933 > 1.98 t-table and a significance value of 0.353 > 0.05 and skills with a t-count of 3.397 > 1.97 t-table and a significant value of 0.001 0.05. Research limitations and implications: This analysis was only carried out in one BP2MI office, and only two dimensions or variables were tested. It is hoped that the implementation of training and skills can be formulated and adapted to the needs of Indonesian migrant workers at BP2MI so that it can be implemented.